(untitled) (London, 1992)
Intensive systems require a high degree of technical and management skill, enabling fish to be produced on a predictable volume basis to correspond with the needs of modern food processing and distribution. Now available in paperback, Intensive Fish Farming explains, at a level suited to both the professional and the student, the environmental requirements of fish, the different husbandry systems used, the problems of reprduction, nutrition and disease control.
Keywords: Fisheries